The values of M and N are -5 and -10 respectively
The equations are given as:
M = 5(x + 1)
N = (6x - 3)
The value of M - N is given as:
M - N = 10
Substitute the known values in the above equation
5(x + 1) - 6x + 3 = 10
Open the brackets
5x + 5 - 6x + 3 = 10
Evaluate the like terms
-x = 2
This gives
x = -2
Substitute x = -2 in M = 5(x + 1) and N = (6x - 3)
So, we have:
M = 5(-2 + 1) = -5
N = (6*-2 - 3) = -15
Hence, the values of M and N are -5 and -10 respectively
Read more about equations at:
https://brainly.com/question/2972832
#SPJ1